ByzRev 08.2026.025: Daphne Penna, Byzantine Law: The Law of the Eastern Roman Empire: (Elements in Rethinking Byzantium). Cambridge: Cambridge University Press 2026 - Morton, James (The Byzantine Review, 2026)
Daphne Penna, Byzantine Law: The Law of the Eastern Roman Empire (Elements in Rethinking Byzantium). Cambridge: Cambridge University Press 2026. 57 pp. – ISBN 978-10-096-9607-4